Evironmental Accounting Disclosure And Financial Sistainability In Listed Negerian Manufacturing Firms - Tamunokonbia Promise Ogan; SILEOLA ADEBUSOLA AKINBOWALE (Indonesian Journal Of Business And Economics, 2021)
With the globalization and dynamic nature of the competitive market environment, manufacturing of quality products at affordable prices no longer guarantee sustainable financial performance, hence firms are now running to sustainability measures to remain financially sustainable. However, manufacturing firms in Nigeria has failed to sustain their performance. Thus, the study was initiated to evaluate the effect of environmental accounting disclosures on financial sustainability of listed Nigerian manufacturing firms. Ex-post facto research design using annual reports of 10 listed manufacturing firms was adopted to achieve the objective of the study. Data was measured using multiple regression analysis. The study revealed that environmental accounting disclosures has insignificant but positive effect on financial sustainability of listed manufacturing firms in Nigeria (Adj. R2 = 0.0468, F- statistics = 1.9721, P-value = 0.0899). With the introduction of the moderating effect of firm size, environmental accounting disclosures showed insignificant but positive effect on financial sustainability of listed manufacturing firms in Nigeria (Adj. R2 = 0.0489, F- statistics = 1.8487, P-value = 0.0981). Thus, the study concluded that environmental accounting disclosures do not have positive but insignificant effect on financial sustainability. It is recommended that the accounting profession should develop standards for reporting environmental accounting information by business entities. At the firm level, there should be voluntary disclosures of environmental accounting information.